The European Institute for Innovation through Health Data. Issue 1 (25th July 2016) - Kalra, D.; Stroetmann, V.; Sundgren, M.; Dupont, D.; Schlünder, I.; Thienpont, G.; Coorevits, P.; De Moor, G.
Abstract: The European Institute for Innovation through Health Data ( i ~HD, www.i‐hd.eu ) has been formed as one of the key sustainable entities arising from the Electronic Health Records for Clinical Research (IMI‐JU‐115189) and SemanticHealthNet (FP7‐288408) projects, in collaboration with several other European projects and initiatives supported by the European Commission. i ~HD is a European not‐for‐profit body, registered in Belgium through Royal Assent. i ~HD has been established to tackle areas of challenge in the successful scaling up of innovations that critically rely on high‐quality and interoperable health data. It will specifically address obstacles and opportunities to using health data by collating, developing, and promoting best practices in information governance and in semantic interoperability. It will help to sustain and propagate the results of health information and communication technology (ICT) research that enables better use of health data, assessing and optimizing their novel value wherever possible. i ~HD has been formed after wide consultation and engagement of many stakeholders to develop methods, solutions, and services that can help to maximize the value obtained by all stakeholders from health data. It will support innovations in health maintenance, health care delivery, and knowledge discovery while ensuring compliance with all legal prerequisites, especially regarding the insurance of patient's privacy protection. It is bringing multiple stakeholder groups together so as to ensure that future solutions serve their collective needs and can be readily adopted affordably and at scale.